Phase chaos and multistability in the discrete Kuramoto model - Maistrenko, V.L.; Vasylenko, A.A.; Maistrenko, Y.L.; Mosekilde, E. (Нелінійні коливання, 2008)
The paper describes the appearance of a novel, a high-dimensional chaotic regime, called phase chaos, in
the discrete Kuramoto model of globally coupled phase oscillators. This type of chaos is observed at small
and intermediate values of the coupling strength. It is caused by the nonlinear interaction of the oscillators,
while the individual oscillators behave periodically when left uncoupled. For the four-dimensional discrete
Kuramoto model we outlined the region of the phase chaos in the parameter plane and distinguished the
region where the phase chaos coexists with other periodic attractors, and demonstrate, in addition, that the
transition to the phase chaos takes place through the torus destruction scenario. Описано виникнення нового багатовимiрного хаотичного режиму, який називають фазовим хаосом, у дискретнiй моделi Курамото глобально зв’язаних фазових осциляторiв. Цей тип хаосу
спостерiгають при малих та середнiх значеннях параметра зв’язку. Вiн спричиняється нелiнiйною взаємодiєю осциляторiв, тодi як поведiнка незв’язаних iндивiдуальних осциляторiв є
перiодичною. Для чотиривимiрної дискретної моделi Курамото окреслено область фазового
хаосу в площинi параметрiв, видiлено область, де фазовий хаос спiвiснує з iншими перiодичними
атракторами, та продемонстровано, що перехiд до фазового хаосу вiдбувається через сценарiй
руйнування тора.